Tindak Pidana Kecelakaan Lalu Lintas yang Mengakibatkan Korban Meninggal Dunia: Studi di Wilayah Hukum Polrestabes Surabaya - Adellra Dwaffa; Karim Karim (Fakultas Hukum Universitas Bhayangkara Surabaya, 2025)
This study examines the investigative procedures applied by the Surabaya Metropolitan Police in handling fatal traffic accidents, with particular focus on how investigators determine the applicable legal provision and establish the form of criminal fault in cases involving alcohol-impaired driving. Employing an empirical legal research method that combines a case approach and a statute approach, data were collected through field interviews with investigators and traffic police officers, supplemented by a systematic literature review. Data were analyzed using a qualitative-descriptive technique. The findings demonstrate that the perpetrator's conduct satisfies the criteria for gross negligence, given that the decision to drive after consuming a significant quantity of alcohol constituted a serious and conscious departure from the standard of care required by law. Furthermore, Article 310 paragraph four of Law Number 22 of 2009 on Road Traffic and Transportation is established as the most appropriate legal provision, as it specifically governs negligent driving causing death under conditions of alcohol impairment, taking precedence over the general negligence provisions of the Criminal Code pursuant to the principle of lex specialis derogat legi generali. Consistent and evidence-based application of the Road Traffic and Transportation Law, incorporating aggravating factors such as driving under the influence, is essential for achieving both justice for victims and a deterrent effect on potential perpetrators.